Lithological Identification Using A Digital Elevation Model (Dem) And Landsat 8 Imagery In The Wasegi Indah Area, Prafi District, Manokwari Regency, West Papua Province - Hezron Kambu; Nur Alzair; Restu Tandirerung (International Journal Labs, 2026)
This study focuses on lithological identification in the Wasegi Indah area, Prafi District, Manokwari Regency, West Papua, using Digital Elevation Model (DEM) and Landsat 8 imagery. Geological surveys traditionally rely on costly and time-consuming fieldwork, but remote sensing technologies, especially DEM and satellite imagery, offer efficient alternatives for geological mapping. This research aimed to process and analyze DEM data alongside Landsat 8 imagery to identify lithological characteristics in the region and compile a lithological boundary map. The study utilized a combination of primary data, including Landsat 8 imagery and DEMNAS data, along with secondary data from geological maps to support geological and lithological interpretation. The results demonstrate that combining Landsat 8 composite images with DEMNAS imagery provides valuable insights into the lithological distribution, aiding in the identification of geological formations such as granite, diorite, and limestone. The findings indicate the potential of remote sensing in geological mapping, although the study also highlights the need for further image processing techniques to improve accuracy. In conclusion, while the lithological maps generated offer regional insights, more detailed mapping is necessary for specific applications like resource exploration and geological hazard management.